JBoss EAP configuration, deployment, and administration - Shepherd, Jason; Safari eBooks ([S.l.] : Packt Pub., 2013)
"JBoss EAP Configuration, Deployment, and Administration is ideal for system administrators and Java application developers. System administrators should have a basic knowledge of Java, but don't require in-depth knowledge about Java development or Java Enterprise Edition. Java Application developers should be familiar with Linux, but not necessarily familiar with previous versions of JBoss. Some exposure to other JEE containers would be useful, but not essential. Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. Master the configuration of JBoss EAP by following practical examples and simplified explanations of its features. This course is full of step-by-step instructions and diagrams to help explain JBoss and Java internals."--Resource description page.
Title from resource description page (viewed Jan. 16, 2014).
Presenter, Jason Shepherd.
Keywords: JBoss; Application software -- Development; Java (Computer program language); Electronic books